Identifying Two Parts of the 1635 Ruthenian Manuscript of the Didactic Gospel - Kravchuk, Denis (Slavistica Vilnensis, 2019)
The article is devoted to the identification of two storage units in the Lviv National Vasyl Stefanyk Scientific Library of Ukraine, which are parts of the once-single Ruthenian Didactic Gospel and, thus, originate from the territory of the Polish-Lithuanian Commonwealth. The identification is made on the basis of the text, the handwriting of the scribe, the number of lines per sheet, and the time of the manuscript creation (1635).